Analisis Keputusan Konsumen Kota Palembang dalam Membeli Tiket Pesawat di Situs Traveloka.com - Revani Agita Putri; Esya Alhadi; Yusleli Herawati (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
The purpose of this research is to know about the influence of brand awareness and brand imageÂ  at Traveloka.com Site to Purchase Decision in Palembang. This research is using the quantitative method and descriptive statistic. The kind of data in this research are primary data from the questionnaire and secondary data is from literature study. The sample in this research is 30 respondents. The sampling technique that used in this research is non probability sampling with purposive sampling. Based on the results t test showed brand awareness has signficant influence on purchase decision. At the same time, brand image has not significant influence on purchase decision. Based on the results F test showed brand awareness and brand image are simultaneously positive and has signficant influence on purchase decision. Traveloka.com must to do innovative approaches to find new things that can build consumer memory and still keep going the positive perception from Traveloka.com.